Analysis of Fine Salt Business in Ketapang Raya Village Keruak District, East Lombok - baiq tania widya purnama (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2020)
The purpose of this study is to analyze (1) Costs and revenues of refined salt business. (2) Feasibility of fine salt business. (3) Constraints faced by entrepreneurs in the fine salt business. The method used in this research is descriptive method. While the determination of the sample area is done by Purposive Sampling and the determination of respondents using the Census method. The results showed that 1) The average cost incurred by fine salt entrepreneurs in Ketapang Raya Village, Keruak District, East Lombok Regency was Rp 29,010,509 / month and income was Rp 3,423,691 / month. 2) The feasibility of refined salt business in Ketapang Raya Village in terms of: a) Technical aspects, refined salt business still uses traditional production processes (boiling). However, the fine salt business is still feasible to try because it provides an income of Rp 3,423,619. b) The financial aspect of explaining that the business of fine salt is feasible, with an R / C ratio of 1.12, which means that the manufacture of fine salt is able to produce costs greater than the cost of capital. With BEP (Break Even Point) receipts of IDR 1,446,783, production BEP of 621 kg and BEP of prices of IDR 2,330 / kg. c) The marketing aspects viewed from the marketing channel found that channel II was more efficient (feasible) because the purchase volume was greater than the marketing channel I. 3) The biggest obstacle faced by fine salt entrepreneurs in Ketapang Raya Village was capital of 14 respondents with a percentage of 70 % and wood as many as 12 respondents with a percentage of 60%.